Melatonin Modulates Lipid Metabolism in Porcine Cumulus–Oocyte Complex via Its Receptors - Zhu, Tianqi; Guan, Shengyu; Lv, Dongying; Zhao, Mengmeng; Yan, Laiqing; Shi, Li; Ji, Pengyun; Zhang, Lu; Liu, Guoshi (Frontiers in Cell and Developmental Biology, 2021)
Lipid is a crucial energy resource for mammalian oocyte. Melatonin could benefit the maturation of porcine oocyte in vitro, but the related mechanism is not elucidated yet. In the current study, methods to monitor lipid metabolism in single live oocytes were firstly established using probes (Lipi-Blue and Lipi-Green). It was observed that both lipid biogenesis and lipolysis occurred in maturing oocyte, but the general level of lipids dropped. Then maturing oocytes stained with probes were treated with melatonin or lipid metabolic-related inhibitors (triacsin C, rotenone, or etomoxir). The results showed that the lipid metabolism and maturation of porcine oocytes were all disrupted and that melatonin rescued the oocytes treated with triacsin C or rotenone, but not those treated with etomoxir. Further investigation demonstrated that cumulus cells are able to transfer lipids to oocytes via gap junctions. It was also observed that melatonin receptors exist in cumulus cells and are required for oocytes to maintain lipid metabolism. Meanwhile, the global gene expressing in cumulus cells was also modulated by melatonin, especially the genes related to antioxidants (SOD1, GPX1, GPX3, GPX4, PRDX2, and PRDX5), lipid metabolism (FABP3, FABP5, ACACB, TECR, etc.), and mitochondrial respiration (GPD1, ETFB, CYC1, and the genes of ATP synthase). Altogether the current research demonstrates that melatonin modulates lipid metabolism in maturing oocytes through its receptors in cumulus cells and benefits the developmental competence of oocytes.